Anatomy of a Civil War Sociopolitical Impacts of the Kurdish Conflict in Turkey - Gurses, Mehmet (University of Michigan Press, 2018)
Anatomy of a Civil War demonstrates the destructive nature of war, ranging from the physical destruction, to a range of psycho-social problems, and to the detrimental effects on the environment. Despite such horrific aspects of war, evidence suggests that civil war is likely to generate multilayered outcomes. To examine the transformative aspects of civil war, Mehmet Gurses draws on an original survey conducted in Turkey, where a Kurdish armed group, the Kurdistan Workers' Party (PKK), has been waging an intermittent insurgency for Kurdish self-rule since 1984. Findings from a probability sample of 2,100 individuals randomly selected from three major Kurdish-populated provinces in the eastern part of Turkey, coupled with insights from face-to-face in-depth interviews with dozens of individuals affected by violence, provide evidence for the multifaceted nature of exposure to violence during civil war.